2017
DOI: 10.1111/joim.12692
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial stress and major cardiovascular events in patients with stable coronary heart disease

Abstract: Abstract. Hagstr€ om E,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 30 publications
(47 reference statements)
1
51
0
1
Order By: Relevance
“…Third, possible confounders cannot be ruled out despite adjustment. 48,49 Fourth, our results reflect an association. The role of hsa_circ_0001445 in the causal pathway of the disease cannot be inferred from our study design, although this knowledge is not a prerequisite for a biomarker.…”
supporting
confidence: 65%
See 1 more Smart Citation
“…Third, possible confounders cannot be ruled out despite adjustment. 48,49 Fourth, our results reflect an association. The role of hsa_circ_0001445 in the causal pathway of the disease cannot be inferred from our study design, although this knowledge is not a prerequisite for a biomarker.…”
supporting
confidence: 65%
“…Second, the incorporation of circRNAs in clinical laboratories is hampered by the fact that research technologies are required for circRNA quantification. Third, possible confounders cannot be ruled out despite adjustment . Fourth, our results reflect an association.…”
Section: Discussionmentioning
confidence: 69%
“…Dear Editor, I read with great interest the article by Hagstr€ om et al [1] about the association between psychosocial stress, such as depressive symptoms, loss of interest, living alone and financial stress, and increased cardiovascular mortality amongst patients with stable coronary heart disease (CHD) despite optimal secondary medical prevention treatment. Although many other contemporary studies have also confirmed the positive correlation of depression with CHD [2,3], an early description of this association is found in the Deuterocanonical Book of the Christian Old Testament, called, according to the translation of the Seventy (Septuagint), Wisdom of Jesus the Son of Sirach (Codex Alexandrinus) or Wisdom of Sirach (Codex Baticanus), also known as the Book of Ecclesiasticus (Latin Church).…”
Section: Sorrow and Cardiovascular Eventsmentioning
confidence: 99%
“…It is indeed fascinating that, already 2000 years ago, the link between sorrow (and perhaps depression) and disease had been observed. The past knowledge on the complex relation between low socio-economic status, depression/being sorrow and heart disease is still, 2000 years later, a growing contemporary problem [2]. Being sorrow could, besides being interpreted as part of a longer standing depression, also reflect a state of more acute emotional stress, such as after the death of a beloved one, sometimes observed causing Takotsubo cardiomyopathy [3].…”
mentioning
confidence: 99%